An Evaluation of the Knowledge, Performance, and Consequence Competence in a Science, Technology, Engineering, and Mathematics (STEM) Based Professional Development for School-based Agricultural Science Teachers: An Assessment of an Industry Supported Com - Saucier, P. Ryan; Langley, G. Curtis (Journal of Agricultural Systems, Technology, and Management, 2017)
Curriculum reform since 1915 has positioned agricultural education as an applied science that combines principles of the physical, chemical, and biological sciences in the production and processing of food and fiber. The agricultural mechanics laboratory is an integral part of agricultural education programs, and instructors are spending a great amount of instructional time in the agricultural mechanics laboratory. Educators have a responsibility to instruct students regarding these specific skills, thus identifying the specific professional development needs of agricultural mechanics instructors can be difficult. The Borich needs assessment model served as the conceptual framework for this study while instrumentation and research objectives were guided by two theories: Bandura’s theory of self-efficacy and Knowles theory of andragogy. Agricultural science teachers from across Texas attended a professional development workshop focused on CNC plasma cutting principles, software, and technology use. Results indicated teachers had professional development needs across all 26 CNC plasma arc cutting competencies and the workshop was effective in lowering these needs based upon a mean weighted discrepancy score. Additionally, when evaluating pre- and post-measures across four summated scales, the importance, knowledge, and ability levels all increased positively.